Carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity and preparation method thereof

By using carbon fiber reinforced ceramic matrix composite materials with low expansion coefficient and low thermal conductivity in the hot end structural materials of gas valves, the transition difference and strength problems existing in existing materials in high temperature environments are solved, and the coordinated optimization of the mechanical properties, thermal expansion properties and thermal conductivity of the material is achieved, and the stability and reliability of the structure are improved.

CN119874395APending Publication Date: 2025-04-25UNIV OF JINAN +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510104247.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing gas valve hot-end structural materials have problems such as material transition, high-temperature strength and loose and slippage in high-temperature environments, which cannot meet the high-temperature usage requirements of solid posture rail-controlled engines.

Method used

Using a carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity, a composite material with excellent mechanical properties and low thermal expansion properties was prepared by immersing carbon fibers in ceramic slurry for ultrasonic impregnation treatment, and multiple impregnation and cracking under vacuum and high pressure conditions.

Benefits of technology

The coordinated optimization of the mechanical properties, thermal expansion properties and thermal conductivity of the material is achieved, and the transition and strength problems of existing materials in high temperature environments are solved, and the stability and reliability of the structure are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874395A_ABST
    Figure CN119874395A_ABST
Patent Text Reader

Abstract

The invention relates to a low-expansion-coefficient low-thermal-conductivity carbon fiber reinforced ceramic-based composite material and a preparation method thereof, and belongs to the field of ceramic-based composite materials. Comprising the following steps: weaving carbon fibers into a continuous carbon fiber preform, soaking in acetone, cleaning with distilled water, and drying in a drying oven; uniformly mixing low-expansion ceramic powder, silicon carbide powder, ultrahigh-temperature ceramic powder and a dispersing agent in deionized water to obtain ceramic slurry; soaking the pretreated continuous carbon fiber preform in the ceramic slurry, impregnating the ceramic slurry into the carbon fiber preform by adopting a vacuum impregnation and ultrasonic impregnation mode, and performing vacuum drying to obtain a ceramic green body; a silicon carbide precursor and an ultrahigh-temperature ceramic precursor are used, a fiber preform is subjected to organic precursor impregnation and cracking, and composite materials with different densities are obtained by controlling impregnation and cracking times. The continuous carbon fiber reinforced ceramic matrix composite material with low expansion coefficient, low heat conductivity coefficient and excellent mechanical property can be obtained, and can be applied to the fields of solid rocket engines and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic-based composite materials, and particularly relates to a low-expansion coefficient and low-thermal conductivity carbon fiber reinforced ceramic-based composite material and a preparation method thereof. Background Art

[0002] Solid rocket engines have attracted attention in the aerospace field because of their simple structure, fast preparation, safety and reliability, and easy storage. Solid attitude and orbit control systems are crucial to aircraft. They are used for attitude, orbit control and terminal guidance, providing powerful power for flight adjustments. The precise regulation of solid attitude and orbit control engines is the cornerstone to ensure that aircraft have high maneuverability and flexibility. Therefore, solid attitude and orbit control engines have become a research focus for global military powers to compete for R&D resources and compete for technological heights. Among them, the hot end structural parts of the gas valve are one of the cores of the solid attitude and orbit control power system. In the valve adjustment process of the solid attitude and orbit control engine, due to the involvement of many complex parameters and mechanisms, it becomes increasingly difficult to accurately predict the engine performance. As the hot end structural parts of the key components responsible for the distribution of high-temperature gas in the system, the gas valve directly determines the main performance level of the attitude and orbit control power system.

[0003] The hot end structural parts of gas valves are always exposed to high-temperature gas environment during operation, so high requirements are placed on the mechanical properties, thermal properties, mechanical erosion resistance and ablation resistance of materials under high temperature conditions. The hot end structural materials of gas valves in service are mainly C / C, C / SiC, SiC / SiC and rare metals such as niobium, thallium and rhenium. Although C / C, C / SiC and other materials are light in weight, their ablation resistance, mechanical erosion resistance, thermal expansion coefficient and thermal conductivity are not ideal; rare metal bases such as niobium, thallium and rhenium have good thermal properties and ablation resistance at high temperatures, but have large thermal expansion coefficients, high thermal conductivity coefficients, and unsatisfactory structural weight reduction, which reduces the stability and reliability of the structure. At the same time, the manufacturing cost is high and the density is large, which cannot meet the needs of technological development. These composite materials and metal coating materials face the problems of poor transition, poor high-temperature strength and local structural loosening and slippage, which greatly hinder the development of solid attitude and orbit control engine technology. Therefore, there is an urgent need to develop new thermal structural materials with low expansion coefficient, low thermal conductivity, excellent anti-oxidation and ablation properties, and anti-mechanical erosion properties to meet their use requirements in high temperature environments.

[0004] Countries around the world have conducted research on ceramic materials with low expansion and low thermal conductivity. Among them, sodium zirconium phosphate materials (NaZr 2 (PO 3 ) 4 ,NZP) is composed of PO 4 and ZrO 6Octahedrons form a three-dimensional network structure with hollows, relaxation and stability in a common vertex manner. The cations can be replaced by a variety of alkali metal and alkaline earth metal ions, thereby deriving a series of isostructural derivatives, collectively referred to as NZP ceramics. By adjusting the composition, the thermal expansion coefficient can be continuously changed from negative to positive, and it has low thermal conductivity, good thermal shock resistance and thermal stability. It is an ideal material for thermal structural components in aerospace and other fields. However, the current NZP phosphate ceramics have problems such as poor mechanical properties and low temperature resistance, and cannot be used for engineering applications. Therefore, how to improve the mechanical properties and temperature resistance of NZP ceramics is a key technical problem that needs to be solved urgently.

[0005] Carbon fiber is currently one of the most promising and effective methods for strengthening ceramic materials. It can essentially overcome the intrinsic brittleness of ceramic materials and improve their resistance to thermal shock. Introducing continuous carbon fibers into the ceramic matrix can change the fracture mode of ceramic materials, that is, from brittle fracture to non-brittle fracture, which can solve the problem of intrinsic brittleness and poor reliability of ceramic materials. At the same time, in order to improve the problem of insufficient antioxidant performance of carbon fibers, by introducing ultra-high temperature ceramic phases, it is expected to achieve the synergy of low thermal expansion of NZP family phosphate materials, "strengthening and toughening" of carbon fibers, and "anti-oxidation" of ultra-high temperature ceramics, so as to meet the use requirements of thermal structural parts of gas valves. However, related research has not yet been reported. Summary of the invention

[0006] In order to solve the deficiencies in the above-mentioned background technology, the present invention discloses a low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and a preparation method thereof. The carbon fiber reinforced ceramic matrix composite material of the present invention has excellent mechanical properties, and takes into account low thermal expansion coefficient and low thermal conductivity, breaks through the difficulty of coordinated optimization of material mechanical properties and thermal properties, and solves the problems of poor material transition, poor high temperature strength and local structural loosening and slippage in gas valve components of existing composite materials and metal coating materials.

[0007] Furthermore, the method for preparing the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material comprises the following steps:

[0008] Step 1: Soak the carbon fiber in acetone for ultrasonic cleaning, then wash it repeatedly with water, and dry it in a vacuum drying oven to remove the surface glue layer;

[0009] Step 2: Weigh low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature ceramic powder, add dispersant, and perform ball milling with deionized water as the medium to obtain a uniformly dispersed ceramic slurry;

[0010] Step 3: Immerse the carbon fiber preform in the ceramic slurry, perform ultrasonic impregnation treatment under vacuum conditions, dry to constant weight after impregnation, repeat the impregnation cycle 2-5 times until the weight no longer increases, and obtain a carbon fiber reinforced ceramic green body;

[0011] Step 4: Soak the carbon fiber reinforced ceramic green body in the ceramic precursor, place it in a sealed container, and perform vacuum impregnation. Then transfer the fiber preform into an autoclave, evacuate it to high pressure, and heat it to solidify the precursor; move the solidified sample to a vacuum carbon tube furnace for high temperature treatment, and obtain carbon fiber reinforced ceramic composites of different densities by controlling the number of impregnation and cracking times.

[0012] Furthermore, the continuous carbon fiber preform in the first step is a needle-punched structure, a three-dimensional braided structure or a 2.5D braided structure, and the fiber volume fraction of the fiber preform is 15-55%.

[0013] Furthermore, in the second step, the low expansion phosphate ceramic powder is one or more of the NZP family compounds, with an average particle size of 50nm-5μm; the average particle size of the silicon carbide powder is 50nm-10μm; the ultra-high temperature powder is selected from one or more of zirconium diboride, zirconium carbide, hafnium carbide, and hafnium diboride; the average particle size of the ultra-high temperature ceramic powder is 50nm-10μm; the mass ratio of low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature powder is 95~60:4~32:1~8.

[0014] Furthermore, the dispersant in the second step is selected from at least one of tetramethylammonium hydroxide, sodium carboxymethyl cellulose, polyethylene glycol, sodium tripolyphosphate and polymethacrylate, the mass of the dispersant is 0.2-5wt% of the mass of the ceramic powder, and the volume fraction of the ceramic slurry is 15-55%.

[0015] Furthermore, in the second step, the ball mill speed is 100-300 r / min, and the ball milling time is 30 min-6 h.

[0016] Furthermore, in the third step, under the condition that the vacuum degree is 1Pa-10Pa, the ultrasonic frequency is 30-140kHZ, and the time is 20min-2h; the drying temperature in the vacuum drying oven is 60-120°C, and the drying time is 4-12h.

[0017] Furthermore, the ceramic precursor in the third step is one or more of polycarbosilane, polyborozirane, polycarbozirane and hafnium boride precursors.

[0018] Furthermore, in the fourth step, the impregnation pressure is 4-10 MPa, the curing temperature is 150-200° C., and the time is 12-24 hours.

[0019] Furthermore, the high temperature cracking temperature in the fourth step is 1100-1500° C., the protective gas is an inert gas, and the insulation time is 1-5 hours.

[0020] Furthermore, the number of times of immersion and cracking in the fourth step is 2-12 times.

[0021] Beneficial effects of the present invention:

[0022] The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof provided by the present invention have the following advantages compared with the prior art:

[0023] 1. The carbon fiber reinforced ceramic matrix composite material prepared by the present invention has a three-point bending strength of 100-160MPa and a fracture toughness of 2.5-5.8MPa·m 1 / 2 The average thermal expansion coefficient is 0.6-2×10 -6 / ℃(100-600℃), thermal conductivity is 0.69-1.5W m -1 / ℃(room temperature).

[0024] 2. The three-dimensional carbon fiber reinforced low expansion ceramic-based composite material prepared by the present invention has a synergistic effect of carbon fiber, low expansion ceramic and ultra-high temperature ceramic multiphase materials, has a low thermal expansion coefficient and thermal conductivity, and has good mechanical properties, achieving a synergistic improvement in the comprehensive performance of the material including mechanical properties, thermal expansion properties and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD spectrum of the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material prepared in Example 1.

[0026] Figure 2 This is a SEM image of the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material prepared in Example 1.

[0027] Figure 3 This is the thermal expansion curve of the carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity prepared in Example 1.

[0028] Figure 4 This is a SEM image of the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material prepared in Example 2. DETAILED DESCRIPTION

[0029] The technical scheme of the embodiment of the present invention will be more clearly explained below in conjunction with the drawings in the embodiment of the present invention. The following description is only a preferred embodiment of the present invention, but is not limited to the following embodiment and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0030] Example 1

[0031] A low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and a preparation method thereof, comprising the following steps:

[0032] The needle-punched carbon fiber preform with a fiber volume fraction of 28% was immersed in acetone for ultrasonic cleaning, then repeatedly washed with water, and dried in a vacuum drying oven to remove the surface glue layer;

[0033] Weigh low expansion CaZr 4 (PO 4 ) 6 The mass ratio of ceramic powder, silicon carbide powder and zirconium diboride powder, low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature powder is 90:8:2, 0.5wt% tetramethylammonium hydroxide is added, and deionized water is used as a medium for ball milling and mixing. The volume fraction of the ceramic slurry is 40%, the ball mill speed is 150r / min, and the ball milling time is 6h to obtain a uniformly dispersed ceramic slurry;

[0034] The carbon fiber preform is immersed in the ceramic slurry, and ultrasonically impregnated under vacuum conditions, with a vacuum degree of 10 Pa, an ultrasonic frequency of 100 kHz, and a time of 30 min. After impregnation, it is dried to a constant weight, and the impregnation cycle is repeated 3 times until the weight no longer increases, thereby obtaining a carbon fiber reinforced low expansion ceramic green body;

[0035] The carbon fiber reinforced ceramic green body is immersed in polycarbosilane, placed in a sealed container, and vacuum impregnated. Then the fiber preform is transferred to an autoclave, evacuated, the impregnation pressure is 6MPa, heated to 150°C, and kept warm for 12 hours to solidify the precursor. The solidified sample is moved to a vacuum carbon tube furnace, the high temperature cracking temperature is 1200°C, the protective gas is argon, the insulation time is 2 hours, and the impregnation cracking times are repeated 4 times to obtain the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material. The XRD spectrum of the continuous carbon fiber reinforced low expansion ceramic matrix composite material obtained in Example 1 is as follows Figure 1 As shown; SEM pictures as Figure 2 As shown; the flexural strength is 160MPa and the fracture toughness is 3.6MPa·m 1 / 2 ; Thermal expansion curves such as Figure 3 As shown, the average thermal expansion coefficient is 0.8×10 -6 / ℃(100-600℃); room temperature thermal conductivity is 0.97W m -1 / ℃.

[0036] Example 2

[0037] A low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and a preparation method thereof, comprising the following steps:

[0038] The needle-punched carbon fiber preform with a fiber volume fraction of 21% was immersed in acetone for ultrasonic cleaning, then repeatedly washed with water, and dried in a vacuum drying oven to remove the surface glue layer;

[0039] Weigh low expansion CaZr 4 (PO 4 ) 6 The mass ratio of ceramic powder, silicon carbide powder and zirconium diboride powder, low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature powder is 80:16:4, 1wt% polyethylene glycol is added, and deionized water is used as the medium for ball milling and mixing. The volume fraction of the ceramic slurry is 35%, the ball mill speed is 200r / min, and the ball milling time is 4h to obtain a uniformly dispersed ceramic slurry;

[0040] The carbon fiber preform is immersed in the ceramic slurry, and ultrasonically impregnated under vacuum conditions. The vacuum degree is 6Pa, the ultrasonic frequency is 120kHZ, and the time is 20min. After impregnation, it is dried to constant weight, and the impregnation cycle is repeated 3 times until the weight no longer increases, thereby obtaining a carbon fiber reinforced low expansion ceramic green body;

[0041] The carbon fiber reinforced ceramic green body is immersed in polycarbosilane, placed in a sealed container, and vacuum impregnated. Then the fiber preform is transferred to an autoclave, evacuated, the impregnation pressure is 8MPa, heated to 180°C, and kept warm for 16 hours to solidify the precursor. The solidified sample is moved to a vacuum carbon tube furnace, the high temperature cracking temperature is 1300°C, the protective gas is argon, the insulation time is 1 hour, and the impregnation cracking times are repeated 5 times to obtain the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material. The SEM image of the continuous carbon fiber reinforced low expansion ceramic matrix composite material obtained in Example 2 is as follows Figure 4 As shown; the flexural strength is 102MPa and the fracture toughness is 2.8MPa·m 1 / 2 ; The average thermal expansion coefficient is 1.6×10 -6 / ℃(100-600℃); room temperature thermal conductivity is 1.3W m -1 / ℃.

[0042] Example 3

[0043] A low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and a preparation method thereof, comprising the following steps:

[0044] The 2.5D structural carbon fiber preform with a fiber content of 30% was immersed in acetone for ultrasonic cleaning, then repeatedly washed with water, and placed in a vacuum drying oven for drying to remove the surface glue layer;

[0045] Weigh low expansion CaZr 4 (PO 4 )6 The mass ratio of ceramic powder, silicon carbide powder and zirconium diboride powder, low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature powder is 95:4:1, 1wt% polyethylene glycol is added, and deionized water is used as the medium for ball milling and mixing. The volume fraction of the ceramic slurry is 42%, the ball mill speed is 150r / min, and the ball milling time is 5h to obtain a uniformly dispersed ceramic slurry;

[0046] The carbon fiber preform is immersed in the ceramic slurry, and ultrasonically impregnated under vacuum conditions. Under the condition of vacuum degree of 8Pa, the ultrasonic frequency is 80kHZ, and the time is 20min. After impregnation, it is dried to constant weight, and the impregnation cycle is repeated 3 times until the weight no longer increases, thereby obtaining a carbon fiber reinforced low expansion ceramic green body;

[0047] The carbon fiber reinforced ceramic green body is immersed in polycarbosilane, placed in a sealed container, and vacuum impregnated. Then the fiber preform is transferred to an autoclave, evacuated, the impregnation pressure is 4MPa, heated to 200°C, and kept warm for 24h to solidify the precursor. The solidified sample is moved to a vacuum carbon tube furnace, the high temperature cracking temperature is 1150°C, the protective gas is argon, the insulation time is 2h, and the impregnation cracking number is repeated 6 times to obtain the low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material. The continuous carbon fiber reinforced low expansion ceramic matrix composite material obtained in Example 2 has a flexural strength of 130MPa and a fracture toughness of 4.5MPa·m 1 / 2 ; The average thermal expansion coefficient is 0.9×10 -6 / ℃(100-600℃); room temperature thermal conductivity is 1W m -1 / ℃.

Claims

1. A carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity and a preparation method thereof, characterized in that: The preparation method comprises the following steps: Step 1: Soak the carbon fiber in acetone for ultrasonic cleaning, then wash it repeatedly with water, and dry it in a vacuum drying oven to remove the surface glue layer; Step 2: Weigh low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature ceramic powder, add dispersant, and perform ball milling with deionized water as the medium to obtain a uniformly dispersed ceramic slurry; Step 3: Immerse the carbon fiber preform in the ceramic slurry, perform ultrasonic impregnation treatment under vacuum conditions, dry to constant weight after impregnation, repeat the impregnation cycle 2-5 times until the weight no longer increases, and obtain a carbon fiber reinforced ceramic green body; Step 4: Soak the carbon fiber reinforced ceramic green body in the ceramic precursor, place it in a sealed container, and perform vacuum impregnation. Then transfer the fiber preform into an autoclave, evacuate it to high pressure, and heat it to solidify the precursor; move the solidified sample to a vacuum carbon tube furnace for high temperature treatment, and obtain carbon fiber reinforced ceramic composites of different densities by controlling the number of impregnation and cracking times.

2. A low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and a preparation method thereof according to claim 1, characterized in that: In the first step, the continuous carbon fiber preform is a needle-punched structure, a three-dimensional braided structure or a 2.5D braided structure, and the fiber volume fraction of the fiber preform is 15-55%.

3. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the second step, the low expansion phosphate ceramic powder is one or more of the NZP family compounds, with an average particle size of 50nm-5μm; the average particle size of the silicon carbide powder is 50nm-10μm; the ultra-high temperature powder is selected from one or more of zirconium diboride, zirconium carbide, hafnium carbide, and hafnium diboride; the average particle size of the ultra-high temperature powder is 50nm-10μm; the mass ratio of low expansion phosphate ceramic powder, silicon carbide powder and ultra-high temperature powder is 95~60:4~32:1~8.

4. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: The dispersant in the second step is selected from at least one of tetramethylammonium hydroxide, sodium carboxymethyl cellulose, polyethylene glycol, sodium tripolyphosphate and polymethacrylate, the mass of the dispersant is 0.2-5wt% of the mass of the ceramic powder, and the volume fraction of the ceramic slurry is 15-55%.

5. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the second step, the ball mill speed is 100-300 r / min, and the ball milling time is 30 min-6 h.

6. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the third step, under the condition of vacuum degree of 1Pa-10Pa, the ultrasonic frequency is 30-140kHZ, and the time is 20min-2h; the drying temperature in the vacuum drying oven is 60-120°C, and the drying time is 4-12h.

7. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the third step, the ceramic precursor is one or more of polycarbosilane, polyborozirane, polycarbozircone and hafnium boride precursors.

8. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the fourth step, the impregnation pressure is 4-10 MPa, the curing temperature is 150-200° C., and the curing time is 12-24 hours.

9. The low expansion coefficient and low thermal conductivity carbon fiber reinforced ceramic matrix composite material and the preparation method thereof according to claim 1, characterized in that: In the fourth step, the high temperature cracking temperature is 1100-1500° C., the protective gas is an inert gas, and the insulation time is 1-5 hours; the number of impregnation cracking times is 2-12 times.

10. A carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity and a preparation method thereof, characterized in that: The composite material is prepared by the method for preparing a carbon fiber reinforced ceramic matrix composite material with low expansion coefficient and low thermal conductivity as claimed in any one of claims 1 to 12.